Using Lichenometry, Dendrochronology, and Historical Data to Establish the Relative Age of an Abandoned Cemetery in Northern Arkansas - Brandy Garrett Kluthe; Margaret Guiccioni; Steven L. Stephenson (Ethnobiology Letters, 2018)
Folklore surrounding an abandoned cemetery located in Johnson County, Arkansas (a part of the Louisiana Purchase) suggested that it was used by early settlers. Historical records were combined with several dating techniques to determine the approximate time periods that Cedar Grove Cemetery was established and abandoned. Cores extracted from trees located adjacent to or on graves provided evidence that the cemetery was abandoned in the 1920s. These results coincide with the last burial event in 1922. The approximate age of undated gravesites was determined using lichenometry. A lichen growth rate of 0.0685 cm/year was determined for lichens present on two gravestones with known dates. This growth rate was then applied to the undated graves to establish their approximate ages. Death dates from historical records of individuals buried in the cemetery matched the dates established by the lichen growth rate. Our results show that many of the unmarked graves date prior to the first documented private ownership of the land. The results of this study support local folklore passed down over several generations about the origin of the cemetery.